2014
DOI: 10.21608/ajfm.2014.18680
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Possible Hepatoprotective Effect of Each of N-acetylcysteine, Coenzyme Q10 and Aloe Vera Gel in Acute Acetaminophen Induced Hepatotoxicity in Albino Rats. (Histological and Biochemical Study)

Abstract: Introduction: Although acetaminophen is a widely used analgesic antipyretic, its toxicity is one of the most common causes of acute liver failure worldwide. N-acetyl cysteine (NAC) is the standard antidote for acute acetaminophen toxicity. Both coenzyme Q10 (CoQ10) and Aloe vera have antioxidant and anti-inflammatory effects so they are used in wide varieties of medical applications Objective: The aim of this work was to compare the possible hepatoprotective effects of NAC, CoQ10 and Aloe vera gel in acute ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…At the same time, it has been studied for its active capabilities, such as hepatoprotective, anti-ulcer, anti-arthritic, and anti-rheumatic properties [109][110][111]. Many investigations have shown that the dental uses of AV are multiple, with a positive impact on the oral area [112][113][114].…”
Section: Biological and Pharmacological Effects Of Aloe Veramentioning
confidence: 99%
“…At the same time, it has been studied for its active capabilities, such as hepatoprotective, anti-ulcer, anti-arthritic, and anti-rheumatic properties [109][110][111]. Many investigations have shown that the dental uses of AV are multiple, with a positive impact on the oral area [112][113][114].…”
Section: Biological and Pharmacological Effects Of Aloe Veramentioning
confidence: 99%